On the historiographic operation: dialogues and possible approaches (Tempo e Argumento, 2012)
This article establishes dialogue and convergence among historians that reflect on the historiographic operation, especially at the present time. The objective is to identify and analyze the political implications of making history, the limits and challenges of this knowledge, as well as the epistemological references that drive the production of the historiographic knowledge. Finally, it highlights the double challenge of unlocking History of its old syllabuses and offers new discussions for the present.
Keywords: writing of history; epistemological challenges; historiography